Comments on the Receptive Theory of Emotion - McCormick, Miriam (Les ateliers de l'éthique / The Ethics Forum, 2024)
These comments focus on chapter 6 of Christine Tappolet’s Philosophy of Emotion: A Contemporary Introduction, asking some questions about her preferred theory, what she calls the “receptive theory of emotions,” and pointing to some areas that could benefit from further clarification.